Characterization of the T4 gp32–ssDNA complex by native, cross-linking, and ultraviolet photodissociation mass spectrometry. Issue 41 (30th September 2021) - Blevins, Molly S.; Walker, Jada N.; Schaub, Jeffrey M.; Finkelstein, Ilya J.; Brodbelt, Jennifer S.
Abstract : Ultraviolet photodissociation and native mass spectrometry allow characterization of the formation and binding interactions of protein-ssDNA complexes. Abstract : Protein–DNA interactions play crucial roles in DNA replication across all living organisms. Here, we apply a suite of mass spectrometry (MS) tools to characterize a protein-ssDNA complex, T4 gp32·ssDNA, with results that both support previous studies and simultaneously uncover novel insight into this non-covalent biological complex. Native mass spectrometry of the protein reveals the co-occurrence of Zn-bound monomers and homodimers, while addition of differing lengths of ssDNA generates a variety of protein:ssDNA complex stoichiometries (1 : 1, 2 : 1, 3 : 1), indicating sequential association of gp32 monomers with ssDNA. Ultraviolet photodissociation (UVPD) mass spectrometry allows characterization of the binding site of the ssDNA within the protein monomer via analysis of holo ions, i.e. ssDNA-containing protein fragments, enabling interrogation of disordered regions of the protein which are inaccessible via traditional crystallographic techniques. Finally, two complementary cross-linking (XL) approaches, bottom-up analysis of the crosslinked complexes as well as MS1 analysis of the intact complexes, are used to showcase the absence of ssDNA binding with the intact cross-linked homodimer and to generate two homodimer gp32 model structures which highlight that the homodimer interface overlaps with the monomer ssDNA-binding site. These models suggest that the homodimer may function in a regulatory capacity by controlling the extent of ssDNA binding of the protein monomer. In sum, this work underscores the utility of a multi-faceted mass spectrometry approach for detailed investigation of non-covalent protein-DNA complexes.